Representasi Nilai-Nilai Sosial Dalam Karungut - Norlaila Norlaila; Paul Diman; Lazarus Linarto; Albertus Poerwaka; Reni Adi Setyoningsih (Universitas Palangka Raya, 2022)
The purpose of this study is to describe the representation of social values in the sack. The problem explored in this research is social values in the form of spiritual values which include (1) truth values, (2) beauty values, (3) moral values, (4) religious values. The method and approach used in this research is a qualitative descriptive approach. Qualitative descriptive approach is used to describe the social values in the karungut. Data analysis of this research was carried out by collecting data with the method of observing and recording, identifying data, classifying data, and describing data. The results of this study indicate that the representation of social values in the karutut with the form of spiritual values shows (a) the truth value in the karungut is the most dominant, there are 29 truth values, namely the values of justice, the value of obedience, the value of decency, the value of craftsmanship, the value of honesty, and the value of responsibility. (b) the value of beauty in the karungut shows 6 values of beauty, namely the value of literary works, the value of dance art and the value of the art of music (c) the moral value in the karungut shows 24 moral values, namely the value of harmony, the value of customs, the value of loving the value of wisdom, data modesty. (d) the religious value in the karungut shows 13 religious values, namely the value of prayer, the value of discipline, and the value of surrender.